1994
DOI: 10.1016/0022-3093(94)90031-0
|View full text |Cite
|
Sign up to set email alerts
|

Sol to gel reaction in the K2OAl2O3SiO2 system

Abstract: A sol to gel transition reaction of three metal alkoxides with water in the preparation of gel in the K20-AleO 3-SiO 2 system was investigated using in situ viscosity measurements and the Raman scattering technique. The viscosity measurements reveal that the viscosity of the solution and the dependence of the reduced viscosity on polymer concentrations change abruptly near the gelation point. The Raman scattering results suggested that the hydrolysis of the TMOS was the rate-limiting step of the overall reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…At the gelation point, the gel phase has lost the ability to flow freely but the system still has the sol fraction which is available for further growth. It was found that the alkoxide was not totally consumed until about the gelation point when Raman spectroscopy was used to follow the disappearance of TMOS as reported in a previous study [19]. The hydrolysis of the alkoxides and condensation of the hydrolysed species produce the primary particles.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…At the gelation point, the gel phase has lost the ability to flow freely but the system still has the sol fraction which is available for further growth. It was found that the alkoxide was not totally consumed until about the gelation point when Raman spectroscopy was used to follow the disappearance of TMOS as reported in a previous study [19]. The hydrolysis of the alkoxides and condensation of the hydrolysed species produce the primary particles.…”
Section: Discussionsupporting
confidence: 51%
“…In the present work we report an in situ small angle X-ray scattering investigation of the sol to gel transition in the K20-AlzO3-SiO 2 system. The composition was chosen to form a monolithic form of feldspar glass as reported in a previous paper [19]. The main goal of the investigation is to obtain quantitative information regarding the structural developments during the sol to gel reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The sol−gel polymerization process of tetraalkoxysilane or silane-coupling agents has been studied as a representative macroscopic sol−gel transition phenomenon. Thus far, and in order to assist application of this process in the industrial arena, discussion has been mainly focused on the property of the gel state rather than on the sol itself. However, since solution processing involves various intermediates or precursors, elucidation of the nature of these precursors may lead to the development of further applications.…”
Section: Introductionmentioning
confidence: 99%
“…The condensation reaction of alkoxides or alkylalkoxides has been extensively applied from sol-gel research to applications in industry. [1][2][3][4][5][6] The reaction involves various intermediates or precursors, although the presence of these species in solution is very dependent upon reaction conditions. Therefore, elucidation of the nature of these species should have potential for further advancement in various applications.…”
Section: Introductionmentioning
confidence: 99%